Long‐term dienogest administration in patients with symptomatic adenomyosis. Issue 8 (29th May 2018) - Neriishi, Kazuaki; Hirata, Tetsuya; Fukuda, Shinya; Izumi, Gentaro; Nakazawa, Akari; Yamamoto, Naoko; Harada, Miyuki; Hirota, Yaushi; Koga, Kaori; Wada‐Hiraike, Osamu; Fujii, Tomoyuki; Osuga, Yutaka
Abstract: Aim: Adenomyosis is a common gynecological disorder that causes dysmenorrhea, hypermenorrhea and metrorrhagia. Previously, we reported that 24 weeks of dienogest treatment is highly effective for pain in symptomatic adenomyosis. Up to present, there is no report that describes treatment of adenomyosis with long‐term dienogest administration for more than 2 years. In this retrospective cohort study, we investigated the course of long‐term dienogest treatment in patients with symptomatic adenomyosis. Methods: This is a retrospective cohort study. Dienogest was continuously administered at a dose of 2 mg daily for patients with symptomatic adenomyosis. The outcome of long‐term administration of dienogest was investigated, and the characteristics of patients were compared between discontinued cases and long‐term administration cases. Results: Two patients were excluded from this study because of transfer to another hospital or discontinuation due to infertility treatment. Twelve of 18 patients (66.7%) received dienogest until menopause or for a period of >80 months. Four cases (22.2%) discontinued dienogest treatment because of severe metrorrhagia. In the discontinued cases because of severe metrorrhagia, the pain score for dysmenorrhea and serum CA125 level at baseline significantly elevated, and the hemoglobin level at baseline and the frequency of type 2 adenomyosis significantly decreased, compared to those with long‐term use. Moreover, long‐term dienogest use did not decrease the serum estradiol level. Conclusion: Our report suggests that dienogest is tolerable for long‐term use until menopause and can be an alternative treatment option in some patients, especially those with type 2 adenomyosis, to avoid hysterectomy.